1989
DOI: 10.1212/wnl.39.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic complications of endocarditis

Abstract: We reviewed the neurologic complications in 113 patients with native and 62 patients with prosthetic valve endocarditis. Neurologic complications occurred with the same frequency (35.3% vs 38.7%) and distribution among the two groups. Death occurred in 20.6% of patients with neurologic complications and in 13.6% of patients without neurologic complications (p = 0.23). Staphylococcus aureus endocarditis correlated statistically with the development of neurologic complications (p less than 0.01) and death (p les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
82
3
9

Year Published

1992
1992
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(108 citation statements)
references
References 0 publications
14
82
3
9
Order By: Relevance
“…Aortic valve disease in our patients was more associated with neurological complications, and this differs from other studies that showed a linkage between mitral valve disease and increased risk of cerebral embolism. 8 Streptococcal species was the most common organism seen in the NC group but was also common in the NNC and is comparable to previous studies. 9 Some reports suggest that Staphylococcus aureus is more associated with neurological complications, particularly thromboembolism.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Aortic valve disease in our patients was more associated with neurological complications, and this differs from other studies that showed a linkage between mitral valve disease and increased risk of cerebral embolism. 8 Streptococcal species was the most common organism seen in the NC group but was also common in the NNC and is comparable to previous studies. 9 Some reports suggest that Staphylococcus aureus is more associated with neurological complications, particularly thromboembolism.…”
Section: Discussionsupporting
confidence: 89%
“…9 Some reports suggest that Staphylococcus aureus is more associated with neurological complications, particularly thromboembolism. 3,6,8 Culture negative and brucella endocarditis were less associated with NC in our studies.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…Intracranial IAs are less common (2-4% of endocarditis cases) but they produce potentially devastating neurological complications such as intracerebral or subarachnoid hemorrhage [9][10][11]. Since IAs can be clinically silent and some of them could resolve by antibiotic therapy, actual incidence of IAs is considered to be higher than the ones reported in the literatures [12].…”
Section: Discussionmentioning
confidence: 98%
“…The most common neurological complication is cerebral stroke, while encephalopathy, central retinal artery blockage, mycotic aneurysms, abscesses, meningitis, and seizures occur less frequently [5,6]. The following factors predispose to neurological complications of IE: heart failure, arrhythmias, abnormal atrioventricular conduction, and the presence of suppurative lesions [4].…”
Section: Medical Studies/studia Medyczne 2016; 32/2mentioning
confidence: 99%